Study of Fixed Point Theorems in Fuzzy Metric Spaces - Rani, Rekha (Innovative Research Thoughts, 2018)
Fixed point theorems are the most important tools for providing existence and uniqueness of the solution of various mathematics models (different, integral, partial differential equation and variational inequalities) representing different phenomena suitable for different fields such as steady state temperature distribution, chemical reaction, neutron transport theory, economic theories, epidemics and flow of fluids. At present this field has been recognized as one of the active field of research.